Type 1 Narcolepsy in Pregnancy: A Case Report and Review of Literature - Yuabov, Asnat; Kilinsky, Alexandra; El Kady, Dina (American Journal of Perinatology Reports, 2024)
Background Type 1 narcolepsy (with cataplexy) is a rare disorder affecting the central nervous system and is characterized by the inability to control sleep–wake cycles. There is a paucity of data regarding management during pregnancy.Case This is a 23-year-old primigravida with narcolepsy and cataplexy, treated with methylphenidate in the third trimester, resulting in an improvement of episodes of cataplexy. A review of the literature reveals information regarding options for medical management and the mode of delivery for these women.Conclusion Type 1 narcolepsy can be treated with medications after consideration of risks and benefits. For patients who are symptomatic at the time of birth, cesarean section may be the preferred mode of delivery in women with type 1 narcolepsy.
Keywords: type 1 narcolepsy; cataplexy; pregnancy; delivery; obstetric; Ceserean Section; medications